2014
DOI: 10.1097/igc.0000000000000276
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Care With Brachytherapy for Cervical Cancer

Abstract: Combination of EBRT and BT for locally advanced cervical cancer continues to decline, despite guidelines indicating the appropriateness of BT. This decline was seen for most regions across the United States, with a concomitant rise in the use of EBRT. EBRT alone is an inferior therapy and must be used in conjunction with BT to realize maximal patient benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The inclusion of brachytherapy in the curative treatment of cervical cancer is essential in improving overall survival 8; 15; 28; 29; 30 . It is a technique that requires skill, trained personnel, special facilities and the need for volume to maintain quality standards 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of brachytherapy in the curative treatment of cervical cancer is essential in improving overall survival 8; 15; 28; 29; 30 . It is a technique that requires skill, trained personnel, special facilities and the need for volume to maintain quality standards 31 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that many women, especially those not in proximity to a high-volume academic center, are often not offered brachytherapy as a part of their cervical cancer treatment regimen or not offered the resources required to find appropriate brachytherapy elsewhere, despite the evidence supporting its survival benefit. 8; 14; 28; 30; 31 Brachytherapy inclusion has been mostly studied in the context of larger treatment regimens, which include surgery and external beam radiation with or without the addition of chemotherapy. We, however, for the first time, demonstrate here the ability of brachytherapy as a single modality treatment to provide a survival advantage for older women with disseminated disease when being used as a palliative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…First, a majority of evidence suggests that BT utilization for CC, in general, has been declining across the nation. 6,[25][26][27] This itself is a result of several factors, including decreased training, a nonevidence-based movement toward noninvasive external beam boost options, and financial incentives favoring alternative radiation treatments. 43 Declining utilization of BT may stem from limited access in patients who are socioeconomically disadvantaged.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24] Despite its profound benefits, BT utilization has declined in the United States with approximately 50% of patients receiving standard-of-care therapy with chemotherapy, EBRT, and BT. 6,[25][26][27] Although a highly effective form of treatment, BT requires increased training, expertise, and effort, but reimbursement for BT has been suggested to be inadequate, thus fueling the decreased utilization. 28 With the looming changes in reimbursement for radiation services with the initiation of the Radiation Oncology Alternative Payment Model (RO-APM) in January 2022, there are increasing concerns regarding this issue and how these changes will affect BT practice patterns and patient care accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Brachytherapy for cervical cancer is complex, time-consuming and requires a skilled team. Despite its important role in the standard of care for cervical cancer (Hanks et al 1983, Eifel et al 2004, brachytherapy utilization is declining (Han et al 2013, Bagshaw et al 2014, Gill et al 2014, which may in part be due to the long procedure times, resource intensiveness, and need for specialized expertise (Ma et al 2019). A large component of brachytherapy procedure time is treatment planning, which is performed real-time while patients are sedated and can take over an hour (Mayadev et al 2014, Michaud et al 2016.…”
Section: Introductionmentioning
confidence: 99%